The gorgeous Georgians - Deary, Terry; Brown, Martin 1959- (London : Scholastic, 1998)
Learn all about the Gorgeous Georgians, like their sneaky schemes for hiding personal hygiene problems and the schoolchildren who went to war with their teachers! With a bold, accessible new look and revised by the author.
Includes index.
Keywords: Great Britain -- History -- 18th century -- Juvenile literature; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile literature; Great Britain -- Social conditions -- 18th century -- Juvenile literature; Great Britain -- Social conditions -- 19th century -- Juvenile literature